Scientific Production and Gender Inequalities in Two Academic Elites: Brazil and Argentina - Beigel, Maria Fernanda (2023)
Despite their relatively similar national contexts, geographical proximity, and comparable historical and cultural experiences, Brazil and Argentina show relevant differences in terms of R&D systems, research assessment procedures and the morphology of their academic elites. However, they share similar paths of integration to the international academic arena, along with the prevalence of nationally oriented groups under a primarily public funding system. Diverse combinations of intersectional inequalities can be found when analyzing two concrete populations of researchers from the Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET) and the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), given that we are dealing with highly internationalized academic elites. In this paper, we describe the two national fields and the target populations in terms of age, position, and institutional affiliation. Considering the different composition by sex of these two populations we observe meaningful analogies regarding publication and, especially, publication in English. Finally, we discuss author positions, showing how intersectional inequalities affect women, relating this general picture to citation impact in Google Scholar and describing how gender territories are built among the top cited researchers.